PRELIMINARY PHYTOCHEMICAL ANALYSIS OF CLEOME VISCOSA – A LESSER EXPLORED CROP OF ECONOMIC IMPORTANCE - SHVETA SAROOP; VEENU KAUL (International Journal of Pharma and Bio Sciences, 2015)
The present investigation reports the phytochemical analyses of Cleome viscosa L. leaves. The bioactive compounds were screened as per standard laboratory procedures and the results evaluated. Extracts of shade dried leaves were prepared in four solvents namely distilled water, methanol, acetone and petroleum ether. The phytochemical analyses revealed the presence of large range of bioactive compounds like alkaloids, flavonoids, tannins, saponins, phenols, sterols, anthocyanides, flavonols, carbohydrates and proteins. However, their intensity differs in each solvent. The results generated can help in extracting important bioactive compounds for consumption and medicinal usage.